PERBANDINGAN KUALITAS LAYANAN KINERJA PERANGKAT JARINGAN TP-LINK WIRELESS N ROUTER DAN GL- INET WIRELESS ROUTER BERBASIS FIRMWARE OPENWRT - Yogi Pratama; Rum Mohamad Andri K. Rasyid (Universitas Amikom Yogyakarta, 2022)
The development of the internet network and network equipment is currently very rapid, to meet the needs of internet usage, network devices are used as supporting tools in service access and network deployment. According to research conducted in a performance comparison analysis between the default firmware and the openwrt firmware [1], the performance of the network device is not only determined by the hardware specifications contained in the network device, but is also determined by the firmware in the network device. according to a literature review from various sources that the openwrt firmware can be used as a firmware solution to improve the performance of network devices that have limited service features and as firmware updates for network devices that do not get development support from vendors.The research will be conducted by analyzing the comparison of the performance of the Gl iNet Wireless Router network device which was created for the openwrt firmware and already using the openwrt firmware from the manufacturer, with the Tp Link Wireless Router network device, which is a network device that will implement the openwrt firmware. The design is carried out using the PPDIOO Life-Cycle Approach network development method, and a comparative analysis of network quality using QoS (Quality of Service) parameters.The final result of this research is how to implement and how the openwrt firmware runs on network devices that are not actually using the original firmware based on the results of network parameters jitter, delay, packet loss, throughput and signal strength testing in internet service access. Keywords : OpenWrt, Quality of Service, PPDIOO, Life-Cycle Approach.